2010
DOI: 10.2353/ajpath.2010.090209
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Type II Pneumocyte-Derived Vascular Endothelial Growth Factor in Alveolar Structure, Acute Inflammation, and Vascular Permeability

Abstract: Vascular endothelial growth factor-A (VEGF) is a potent regulator of vascular permeability, inflammatory response, and cell survival in the lung. To explore the functions of VEGF produced locally in type II pneumocytes, we generated mice with a conditional deletion of VEGF-A using Cre recombinase driven by the human surfactant protein C (SPC) promoter. In 7-to 10-week-old VEGF-knockout (SPC-VEGF-KO) mice, lung histology and physiology were essentially normal, except for higher dynamic lung compliance and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 54 publications
1
35
0
1
Order By: Relevance
“…However, alveolar type II cells are considered to be local progenitor cells that have the ability to compensate for the loss of type I cells and are resistant to apoptotic signals (28). Because growing evidence suggests that impaired repair of alveoli is a critical mechanism in emphysema (10,21), it will be interesting to analyze the response of both type I and type II alveolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, alveolar type II cells are considered to be local progenitor cells that have the ability to compensate for the loss of type I cells and are resistant to apoptotic signals (28). Because growing evidence suggests that impaired repair of alveoli is a critical mechanism in emphysema (10,21), it will be interesting to analyze the response of both type I and type II alveolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…A-aDO 2 should be increased proportionally by the reduced surface and integrity of AECs. Recently, injury of AECs has been of great concern as the primary pathogenesis of smoking-induced PE (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)31,35,36). A recent ultrastructural study showed early disruption of AECs to be associated with smoking-induced chronic inflammatory processes and regional hypoxia (1,3,31).…”
Section: Rgbmentioning
confidence: 99%
“…A second transgenic mouse line carrying a similar Sftpc-cre transgene has also been generated in order to be breed with a Vegf conditional mutant mouse line (Mura et al, 2010). According to the data reported, the lungs of 7-to 10-week-old Vegf fl/fl ; Sftpc-cre 1 mutant mice showed normal appearance and histology, indicating no detectable deleterious effect of this Cre transgene.…”
Section: Fig 2 Comparative Histology Of Lung Morphology From Stfpc-crementioning
confidence: 99%
“…This second Sftpc-cre mouse strain was established in the ICR genetic background. The difference in behavior of the two transgenic lines can either be due to variation in the genetic background, or more likely, to distinct random integration event of the transgene in the genome that can affect transgene expression levels (Matthaei, 2007;Mura et al, 2010;Okudo et al, 2005).…”
Section: Fig 2 Comparative Histology Of Lung Morphology From Stfpc-crementioning
confidence: 99%